THE RELATION OF GEOGENIC AND ANTROPHOGENIC FACTORS WITH BLOOD AND HAIR LEAD AND ARSENIC LEVELS IN WOMEN LIVING IN CAN AND BAYRAMIC DISTRICTS OF CANAKKALE PROVINCE - (:unkn) unknown (NOBEL ILAC, 2019)
Objective: Mining areas and associated industrial activities carry considerable risks for human health due to multi-pathway exposure of heavy metals such as arsenic and lead. The objective of this study was to compare arsenic and lead levels it human blood and hair samples in all industrial mining area in northwestern Turkey with that of non-exposed group demonstrating similar sociocultural characteristics. Material and Method: The population of the study consisted of 674 nonsmoker women over the age of 40 who were selected on random basis from mine region and control area. Venous blood samples were taken and analyzed fur blood lead and arsenic levels in all participants. Hair samples were later collected from 108 women with high levels in blood samples. Results: The results showed that the highest prevalence of occurrences was found in district centers whereas relatively lower values were observed in the villages. Hail arsenic and lead levels were comparably higher in the industrialized area (can Region) where low-quality coal combustion used in power generation and residential heating were dominant. Conclusion: Although high correlations were not found, blood and hair arsenic and lead levels in individuals living in industrial in agricultural areas were found to he high at levels influencing the human health On the other hand, these results should be further supported and verified with advanced and long duration monitoring activities.
Keywords: Arsenic; lead; medical geology; human health; anthropogenic factors; HUMAN HEALTH; GEOTHERMAL SYSTEMS; WATER; TURKEY; IMPACT; CONTAMINATION; EXCRETION; EXPOSURE; ADULTS; RISK